Interactive Generation of Oral History by a Child with Participation of an Adult - N. M. Yurieva (Научный диалог, 2022)
The article deals with the interactive narrative patterns that arise in the course of telling stories by children with the participation of an adult. The relevance of the study is due to the need to develop a theory of discursive development during preschool childhood as an important component of knowledge about speech ontogenesis and the features of the formation of narrative competence. The novelty of the research is seen in the fact that the theory of speech ontogenesis introduces the idea of the complex nature of the formation of narrative skills in speech ontogenesis, which are of a long-term nature and are not limited only to the assimilation of linguistic material by children, the improvement of syntax and syntactic structures. New data that receive theoretical understanding on the basis of a cognitive-discursive approach and a hypothesis about the interactive nature of narrative discourse in speech ontogenesis are introduced in the article. The concept of an interactive dialogical pattern is explained, which means dialogical constructions jointly built by an adult and a child, through which the internal experience, images, impressions of the visually presented story are analyzed and formulated by the participants in the storytelling situation. It is shown that the dialogical patterns that arise in the child's telling a story with the participation of an adult are a discursive mechanism that contributes to the creation of oral history by the child through the “mobilization” of the child's potential discursive capabilities, which are activated in the dialogue.